ANALISIS MANAJEMEN LABA KAITANNYA DENGAN NILAI PERUSAHAAN SEBELUM DAN SESUDAH IPO PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Dyah Ayu Retno Inten, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
The purpose of this research is to examine earnings management surrounding IPO, firm value and the association of earnings management surrounding IPO with firm value. The objective of this study is to obtain empirical evidence about manufacturing companies listed in Indonesia Stock Exchange performing earning management during IPO that in the year of IPO , in the fist year IPO taking place. The study also found the association between earning management surrounding IPO and firm value. The research variables examined in this study are earning management indicated by Discretionary Accrual (DA) and firm value by Tobin (Q).